2015
DOI: 10.7314/apjcp.2015.16.11.4537
|View full text |Cite
|
Sign up to set email alerts
|

OK-432 Suppresses Proliferation and Metastasis by Tumor Associated Macrophages in Bladder Cancer

Abstract: OK-432, a Streptococcus-derived anticancer immunotherapeutic agent, has been applied in clinic for many years and achieved great progress in various cancers. In the present study, we investigated its anticancer effect on bladder cancer through tumor associated macrophages (TAMs). MTS assay validated OK-432 could inhibit proliferation in both T24 and EJ bladder cell lines. OK-432 also induced apoptosis of bladder cancer cells in vitro. Consequently, we demonstrated that OK-432 could suppress the bladder cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Furthermore, the optimal dose of intratumoural OK-432 injection is yet to be validated. We used 0.075 KE (0.5 KE/kg) in the present study based on a previous report 34 . As a result, we indicated that the efficacy of OK-432 was approximately equivalent to that of RFA, while various authors had reported that the efficacy of OK-432 was slightly weaker than that of RFA 25,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the optimal dose of intratumoural OK-432 injection is yet to be validated. We used 0.075 KE (0.5 KE/kg) in the present study based on a previous report 34 . As a result, we indicated that the efficacy of OK-432 was approximately equivalent to that of RFA, while various authors had reported that the efficacy of OK-432 was slightly weaker than that of RFA 25,35 .…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that EC has an active role in promoting cancer cell proliferation, survival, migration and invasion. A number of previous reports suggested a role for macrophages (26,27) and neutrophils (28) in the progression of bladder cancer. However, the role of ECs in the tumor microenvironment in bladder cancer is only beginning to be unveiled.…”
Section: Discussionmentioning
confidence: 99%
“…In our center (Department of Urology, First Affiliated Hospital of Sun Yat-sen University), good results have been achieved in preventing recurrence and progression of NMIBC by administering OK-432 as an intravesical immunotherapeutic agent (22). Previous studies have proposed that the primary antitumor role of OK-432 in bladder carcinoma involves mobilization of the cellular immune system by activating macrophages, NK cells, lymphokine-activated killer cells and various T cells (23,24). Secondary roles include increasing the binding capacity of these cells to the tumor cells, thereby enhancing the antitumor effect (25).…”
Section: Discussionmentioning
confidence: 99%